PENGEMBANGAN MEDIA FLASH CARD TERHADAP KEMAMPUAN BERHITUNG SISWA TUNAGRAHITA DI SEKOLAH DASAR - Risma Pratiwi Galingging; Ery Rahmawati; Galuh Kartika Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Children with intellectual disabilities are those whose cognitive abilities are below average compared to other students. One of the areas where they struggle is in arithmetic, and with the advancement of technology, engaging media is needed. The purpose of this study is to determine the suitability of flash cards for the arithmetic abilities of students with intellectual disabilities and their response to the flash cards used. The development model used by the researcher is the R&D Borg and Gall research and development model. Five students with intellectual disabilities at SDN Lemah Putro 1 were the subjects of the study. The media validation scored 84% (very feasible) based on the calculation results, while the material validation scored 91% (very feasible). Student learning outcomes also improved, with an average pre-test score of 56 (category: poor) and an average post-test score of 79.2. The N-Gain calculation showed an average value of 0.527, which falls into the moderate category. This indicates that the developed flash card media is effective in assisting students with intellectual disabilities in their learning. Therefore, it can be concluded that the flash card media is well-received by students at SDN Lemah Putro 1, and student responses when using the flash card media scored 89.2, categorized as highly appropriate.